The relationship between physical exercise and subjective well-being in Chinese older people: The mediating role of the sense of meaning in life and self-esteem - Chen, Rui; Liu, Yong-Feng; Huang, Gao-Duan; Wu, Peng-Cheng (Frontiers in Psychology, 2022)
Purpose This study explores the relationship between physical exercise and older people’s subjective well-being and the mediating role of a sense of meaning in life and self-esteem by using a structural equation modeling (SEM) approach, in order to provide some suggestions for improving older people’s subjective well-being. Methods In this study, a cross-sectional survey was conducted offline using a simple random method of collection, and the Physical Activity Rating Scale (PARS-3), the Subjective Well-being Scale (SWB), the Meaningfulness of Life Scale (MLQ), and the Self-Esteem Scale (SES) were applied to 419 older adults who participated in physical exercise from Chengdu (Qingyang District, Wuhou District, and Chenghua District), Sichuan Province, China, with the voluntary participation of the subjects. 197 males and 222 females, with a mean age of 72.49 (SD = 1.57). The study used SPSS 25.0 and Process 3.5 plug-in for statistical processing of the data, Cronbach’s alpha coefficient for intra-variate consistency testing, Harman’s one-way test for common method bias testing and multiple covariance diagnosis, and finally regression analysis and Bootstrap sampling test for significance of mediating effects. Results Physical exercise was able to have a positive effect on the level of subjective well-being of older adults (β = 0.0305; 95% confidence interval (CI): 0.0226, 0.0384; p < 0.05), and a mediation analysis of sense of meaning in life and self-esteem revealed that they were able to have independent and chained mediation effects, with four pathways: first, physical exercise directly affected subjective well-being of older adults (β = 0.0149; 95% CI: 0.0072, 0.0226; p < 0.05; β = 0.0149; 95% CI: 0.0072, 0.0226; p < 0.05); secondly, sense of meaning in life mediated the relationship between physical exercise and subjective well-being of older adults (β = 0.0075; 95% CI: 0.0041, 0.0115; p < 0.05); thirdly, self-esteem mediated the relationship between physical exercise and subjective well-being of older adults (β = 0.0075; 95% CI: 0.0041, 0.0115; p < 0.05). (β = 0.0061; 95% CI: 0.0034, 0.0094; p < 0.05); fourth, a chain mediating effect of sense of meaning in life and self-esteem in the relationship between physical exercise and subjective well-being in older adults (β = 0.0021; 95% CI: 0.0010, 0.0035; p < 0.05). Conclusion and prospects As indicated by the results, physical exercise can enhance the subjective well-being of older adults through sense of meaning in life and self-esteem, therefore, in order to be able to enhance the subjective well-being of older adults, enhancing the level of sense of meaning in life and self-esteem of older adults is an effective means.